Cutaneous anthrax leading to corneal scarring from cicatricial ectropion. Issue 10 (October 1989) - Yorston, D; Foster, A
Abstract : Eleven patients with cutaneous anthrax of the eyelids are presented. The complications were cicatricial ectropion (eight patients), resulting in corneal scarring (three patients). The ectropion was corrected by full thickness postauricular skin grafts, with good results. The predilection of this infection for the eyelids of young children and a seasonal variation suggest that a vector may be involved in transmission.